Achieving Life Milestones in Duchenne/Becker Muscular Dystrophy: A Retrospective Analysis. Issue 4 (August 2021) - Donaldson, Andrew; Guntrum, Debra; Ciafaloni, Emma; Statland, Jeffrey
Abstract : Objective: To understand the milestones achieved in the transition from childhood to adulthood for patients with Duchenne and Becker muscular dystrophies (DMD/BMD). Methods: We performed a retrospective chart review on patients aged 15 years or older with a clinical diagnosis of DMD/BMD who received care from January 1, 2008, to January 1, 2018 at the University of Kansas Medical Center and the University of Rochester Medical Center. Participants were identified using local Muscular Dystrophy Asssociation-funded clinic lists, neuromuscular research databases, and electronic medical record review. Data were abstracted using a uniform template on education, employment, community resources, relationships, and end-of-life discussions and is presented as mean, median, or frequency with associated 95% confidence interval (CI). Results: A total of 109 patients were identified: patients ranged in age from 15 to 56 years with a median of 24, and covered a 5-state region and Ontario, Canada. Seventy-eight percent of patients had DMD and were, on average, 8.5 years younger than patients with BMD. Over half (56.9%, 95% CI 47.6–66.2) were high school graduates or beyond. Sixteen percent did not have their highest level of education documented. Only 20.0% had an occupation (95% CI 12.7–27.7), most frequently in education and administrative support (34%). The majority were still living with parents (80.7%, 95% CI 73.3–88.1). A minority reported having end-of-life discussions (17.4%, 95% CI 10.3–24.6). Conclusions: Psychosocial elements reflecting the transition to adulthood are inconsistently reported in clinical documentation. A prospective study will further elucidate this transition.